Outdoor Lighting and the Effects of Artificial Light at Night (ALAN) - Satzler, Stacia (Kansas State University. K-State Libraries, 2021)
As Light Emitting Diodes (LEDs) are replacing High Pressure Sodium (HPS) street lights, some groups have concerns about the health and environmental effects of blue-rich LED lights. The AMA released a report recommending that all street lighting have a CCT of less than 3000K, but other organizations felt this threshold was arbitrary and unfounded. To shed light on this dispute, I researched the effects of artificial light at night (ALAN), particularly concerning LED lights, to determine what policies design companies should set concerning outdoor lighting. I have learned that artificial light at night (ALAN) has been linked to many serious health conditions, including diabetes, cancer, heart disease, obesity, and depression. Light sources with high intensities of 450-500 nm light disrupt our bodies’ circadian rhythm and make it more difficult for our eyes to adjust to darkness. LEDs, even low-CCT LEDs, have a spike in intensity in that range. Studies have also shown that sources with high blue light content impact natural photosynthesis cycles, disrupt animal behavior, and affect skyglow and star visibility much more severely than warmer sources like HPS. Unfortunately, I also discovered that CCT, often the only metric that manufacturers release about the light source in a luminaire, is a poor descriptor of blue light content. On average, higher-CCT sources will have higher levels of blue light, but two sources with the same CCT can have wildly different levels of blue light, meaning that a designer cannot know the effects of the light source they choose. This presents a challenge and an opportunity for lighting designers. To provide exceptional design to clients, designers will need to be pioneers in calling for new light sources and metrics to describe spectral distribution, while continuing to serve their clients excellently with limited information.
Kirmser Undergraduate Research Award - Individual Non-Freshman category, honorable mention
Keywords: Outdoor Lighting; Artificial Light At Night (ALAN); Light Emitting Diodes (LED); High Pressure Sodium (HPS); Street Lights; Blue Light Effects